Effect of eyestalk ablation on moulting and growth in the mudspiny lobster Panulirus polyphagus (Herbst, 1793) held in captivity - Kizhakudan, Joe K. (Indian Journal of Fisheries, 2013)
The effect of eyestalk ablation on moulting and growth in juveniles (20-40 mm carapace length, CL) and sub-adults (50â€“70 mm CL) of the mudspiny lobster Panulirus polyphagus was assessed through laboratory experiments. Eyestalk ablation resulted in increased frequency of moulting in juvenile and sub-adult males and females. Ablated lobsters showed a higher rate of growth at each moult as compared to the unablated ones. Growth increment, in terms of both carapace length and weight, was particularly high among the juvenile males. Ablated juvenile males showed an average increase in CL by almost 74% in about 114 days (0.7% increment per day) while the unablated ones showed an increase in CL of about 45% in 115 days (0.4% increment per day). Ablated juvenile males showed maximum weight gain of 370% in 114 days (3.3% per day) while control males showed an increase of 174% in 115 days (1.5% per day). The percentage increase in CL showed a decreasing trend with size in all the animals. Analysis of variance of the growth increments in terms of CL revealed significant difference (âˆž=0.05) between the growth rates of ablated and control juvenile males and between the ablated juvenile males and females.